How can African agriculture adapt to climate change: Global carbon markets: Are there opportunities for Sub-Saharan Africa? - Bryan, Elizabeth; Akpalu, Wisdom; Ringler, Claudia; Yesuf, Mahmud (International Food Policy Research Institute, 2008)
Human activities such as fossil fuel burning and deforestation have significantly increased the atmospheric concentration of greenhouse gases (GHG) leading to global climate change. Global climate change and its associated weather extremes pose considerable challenges worldwide, and mitigating the adverse impacts of climate change is a high priority for the international community. To reduce global emissions and curb the threat of climate change, many countries are participating in carbon trading. Carbon trading includes allowance-based agreements that impose national caps on emissions and allow participating countries to engage in emission trading as well as project-based transactions (for example, through the CDM or Clean Development Mechanism). The CDM allows industrialized countries with greenhouse gas reduction commitments to invest in emission-reducing projects in developing countries as an alternative to generally more costly emission reductions in their own countries. Funds made available by the CDM for carbon offsets provide an opportunity for cash-strapped developing countries to fund much needed adaptation measures. The potential annual value stream for Sub-Saharan Africa from mitigating GHG emissions is estimated to be US$4.8 billion at carbon prices of US$0–20/tCO2e. Moreover, agricultural mitigation measures, including soil and water conservation and agroforestry practices, also enhance ecosystem functioning, providing resilience against droughts, pests, and climate-related shocks. Yet the potential for Africa to contribute to global reductions in GHG emissions is quite substantial. Estimates suggest Africa could potentially contribute to GHG reductions of 265 MtCO2e (million tons of carbon dioxide or equivalent) per year at carbon prices of up to US$20 through agricultural measures and 1,925 MtCO2e/yr at carbon prices of up to US$100/tCO2e by 2030 through changes in the forestry sector. These amounts constitute 17 and 14 percent, respectively, of the global total potential for mitigation in these sectors. However, countries in Sub-Saharan Africa are marginalized in global carbon markets. Sub-Saharan Africa’s share of the CDM market is nine times smaller than its global share of GHG emissions, including emissions from land use and land-use change. This brief is based on a paper that examines Sub-Saharan Africa’s current involvement in carbon markets, potential for GHG emission reductions, constraints to further participation in carbon markets, and opportunities for expanding Sub-Saharan Africa’s market share.